Unveiling the Effect of Superlattice Interfaces and Intermixing on Phase Change Memory Performance - Khan, Asir Intisar; Wu, Xiangjin; Perez, Christopher; Won, Byoungjun; Kim, Kangsik; Ramesh, Pranav; Kwon, Heungdong; Tung, Maryann C.; Lee, Zonghoon; Oh, Il Kwon; Saraswat, Krishna; Asheghi, Mehdi; et al. (Nano Letters, 2022)
Superlattice (SL) phase change materials have shown promise to reduce the switching current and resistance drift of phase change memory (PCM). However, the effects of internal SL interfaces and intermixing on PCM performance remain unexplored, although these are essential to understand and ensure reliable memory operation. Here, using nanometer-thin layers of Ge2Sb2Te5 and Sb2Te3 in SL-PCM, we uncover that both switching current density (Jreset) and resistance drift coefficient (v) decrease as the SL period thickness is reduced (i.e., higher interface density); however, interface intermixing within the SL increases both. The signatures of distinct versus intermixed interfaces also show up in transmission electron microscopy, X-ray diffraction, and thermal conductivity measurements of our SL films. Combining the lessons learned, we simultaneously achieve low Jreset ≈ 3-4 MA/cm2 and ultralow v ≈ 0.002 in mushroom-cell SL-PCM with ∼110 nm bottom contact diameter, thus advancing SL-PCM technology for high-density storage and neuromorphic applications.
Keywords: Memory operations; Memory performance; Phase-change memory; Resistance drifts; Sb2te3/ge2sb2te5superlattice; Superlattice interface; Superlattice intermixing; Switching current density; Switching currents; Thin layers; Thermal Conductivity; X-Ray Diffraction; phase-change memory; resistance drift; Sb2Te3/Ge2Sb2Te5superlattice; superlattice interface; superlattice intermixing; switching current density